METHODOLOGY FOR COMPREHENSIVE ASSESSMENT OF RELIABILITY INDICATORS OF ELECTRONIC COMMUNICATION EQUIPMENT WITH COMBINED TIME REDUNDANCY - TYKHONOV, MYKOLA; KONONOVA, IRYNA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article considers the urgent task of a comprehensive assessment of reliability indicators of electronic communication equipment with combined time redundancy in order to increase the efficiency of their operation and ensure a given level of reliability. The comprehensiveness of the approach is ensured by the joint consideration of a number of factors affecting the reliability of the equipment. These factors include: limited reliability of hardware and software, the presence of impairing and nonimpaired failures, the use of replenishable and nonreplenishable components of the time reserve, the division of tasks into stages with intermediate storage of results, and the level of qualification of the operating personnel. At the first stage of the developed methodology, the features of the functioning of electronic communication equipment with a combined time reserve are analyzed. Two sources of the time reserve are identified: a replenishable reserve (functional inertia) and a non-replenishable reserve (additional operational time or performance reserve). The mechanism for checking time constraints at each stage of functioning is considered, which allows achieving the effect of “dilution” of the failure stream. At the second stage of the methodology, the expediency of decomposing the general model of functioning into two partial models - for the replenishable and non-replenishable components of the time reserve - is substantiated. This approach simplifies the construction of the mathematical apparatus and provides a synthesis of partial results for further analysis. In the subsequent stages, a scientific and methodological apparatus for reliability assessment is formed, taking into account various factors, in particular in cases of complete and limited initial information. For the latter case, an approach to constructing bilateral estimates of reliability indicators using the basic functionality is proposed. Scientifically based recommendations on ways to improve the reliability of electronic communication equipment are formulated. In particular, the effectiveness of combined time reservation is proved, provided that its components are rationally combined. Methods of reducing the impairment of developments are proposed, in particular by dividing tasks into stages and optimizing their number. The obtained results can be used in engineering practice in the design and modernization of electronic communication equipment.